ANALISIS TEKNIK PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH DITINJAU DARI TEOLOGI, FILOSOFI, PSIKOLOGI, DAN SOSIOLOGI PENDIDIKAN - Toto Suryadi; M. Asif Nur Fauzi; Lukmansyah Lukmansyah (Educatus, 2025)
Educational institutions are institutions that have a large target in the realization of education in accordance with the mandate of the national education goals, namely the development of students' self-potential to become individuals who believe and fear God and be able to compete globally. The magnitude of the challenge is supported by the dynamics of changing times which are very fast changing. The challenge is not only in the knowledge sector but also the morale and competency competitiveness of graduates. The achievement indicator depends on the right decision making by the school principal. This research was conducted using the library research method. Based on the context analysis carried out, theologically, decision-making must be done by deliberation because the considerations in the decisions taken are obtained from the core organization of the educational institution. If studied from a philosophical aspect, then the basis of empiricism is needed in decision making so that it is rational. If examined from the psychological aspect of decision making, it includes the role of a group of people in determining alternative decisions to be taken so that the consequences can be solved together. If examined from a sociological perspective, decision making must be based on internal and external analysis so that the decisions taken are able to respond to the dynamic demands of the times. Therefore, it is recommended for school principals in making decisions to use a transactional leadership style that prioritizes analysis of the situation and condition of the institution and prioritizes mutual agreement.